2010
DOI: 10.1111/j.1743-6109.2009.01669.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cell Number in the Bed Nucleus of the Stria Terminalis of Mice: Role of Testosterone Metabolites and Estrogen Receptor Subtypes

Abstract: Introduction The bed nucleus of the stria terminalis (BNST) exhibits several sex differences that may be related to male sexual behavior and gender identity. In mice and rats, sex differences in the principal nucleus of the BNST (BNSTp) are due to sexually dimorphic cell death during perinatal life. Although testosterone treatment of newborn female rats increases BNSTp cell number, the relevant hormone metabolite(s) are not known, and the effect of testosterone on the development of BNSTp cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 64 publications
3
67
1
Order By: Relevance
“…Also, a study using female mice did not clearly determine whether postnatal EB treatment can masculinize the volume of female BNSTp because it showed that BNSTp volume in adulthood was increased by subcutaneous injection of EB into newborn females, but it also showed no effect of this same treatment [18]. However, this previous report clearly demonstrated that EB treatment could increase the number of BNSTp neurons in female mice [18]. There are several possible hypotheses that could explain why postnatal EB treatment did not restore BNSTp volume in male ArKO mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, a study using female mice did not clearly determine whether postnatal EB treatment can masculinize the volume of female BNSTp because it showed that BNSTp volume in adulthood was increased by subcutaneous injection of EB into newborn females, but it also showed no effect of this same treatment [18]. However, this previous report clearly demonstrated that EB treatment could increase the number of BNSTp neurons in female mice [18]. There are several possible hypotheses that could explain why postnatal EB treatment did not restore BNSTp volume in male ArKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that estrogen functions during the early postnatal period to maintain neuron number of the BNSTp in male mice. Also, in female mice, postnatal EB treatment has been shown to increase the number of BNSTp neurons [18]. Neurons expressing aromatase are located in the BNSTp of rats during the late prenatal period to the early postnatal period [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Newborn male, female, and androgenized female mice were given saline or valproic acid and effects on the principal nucleus of the BNST (BNSTp) were determined at weaning (Murray et al, 2009). The BNSTp exhibits a number of morphological and neurochemical sex differences in rodents and humans (Guillamon et al, 1988; Hines et al, 1985; Forger et al, 2004; Allen & Gorski, 1990), and in mice these differences can be eliminated by giving females a single injection of testosterone propionate on the day of birth (Hisasue et al, 2010). Valproic acid treatment transiently increased histone acetylation in the brain and prevented masculinization of BNSTp cell number in both males and testosterone-treated females (Murray et al, 2009).…”
Section: Introductionmentioning
confidence: 99%